Fuzzy Based Analysis of Inverter Fed Micro Grid in Islanding Operation-Experimental Analysis - Yuvaraja Teekaraman; Gopinath Mani (International Journal of Power Electronics and Drive Systems (IJPEDS), 2015)
Islanding operation in essence connotes isolating part of a power system not unlike distributed generation. This thesis puts forward fuzzy logic controller for inverter fed micro-grid in islanding operations which is assessed using hardware implementation. It’s assisted by power electronics which imparts the control and flexibility essential for the micro grid concept. A correctly designed controller guarantees that the micro grid can meet its utility’s demands. The efficacy and robustness is deliberated in the design of fuzzy system. The testing is performed by employing hardware components namelyATMEGA-328microcontroller, TLP250 opto-coupler and a MOSFET circuit. The test results demonstrate very good consistency and show noteworthy implications of the control of micro grid using inverters and fuzzy controllers.